Fabrication of Nutraceutical Beverage from Saffron (Crocus sativus L.) Extract and Studying Its Health Effects - Qaswaa Yousif Jameel; Nameer Khairullah Mohammed; Mohammed Abdullah Ajeel (International Journal of Food Science)
A saffron extract-based beverage (SEBB) was formulated and characterized based on its sensory attributes and health benefits. The main bioactive compounds of saffron extract (crocin and safranal) were quantified. Three formulations of SEBB were prepared based on the sucrose concentration: SEBB 1 contained 65 g of sucrose per 500 ml, SEBB 2 contained 17.5 g, and SEBB 3 contained 79.5 g. The SEBB most desired by consumers was then subjected to biochemical analysis to evaluate its antioxidative effects on the damage induced by food contaminated with carbon tetrachloride (CCl4). Fifteen albino rats were split into five groups and treated with different doses of CCl4 or SEBB according to the planned animal experiment for 62 days. Sensory evaluation illustrated that SEBB 1 had the highest acceptability scores. The content of crocin and safranal was 23.039 and 4.135 ppm, respectively. The SEBB ameliorated the increased activity of enzymes involved in liver and kidney function and improved the total antioxidant capacity, blood glucose, and lipid profile.